2015
DOI: 10.1097/shk.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Severe Lymphopenia Is Associated with Elevated Plasma Interleukin-15 Levels and Increased Mortality During Severe Sepsis

Abstract: Sepsis-related mortality has been found increased in RAG-1 knockout mice. However, in patients admitted to medical intensive care units, it is unknown whether severe lymphocyte depletion at admission is associated with increased interleukin (IL)-7 and IL-15 levels in circulation, and increased mortality. We prospectively enrolled 92 patients who were admitted to medical intensive care units for severe sepsis or septic shock. At admission, 24 patients (26.1%) had severe lymphopenia, defined as lymphocyte counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 31 publications
(41 reference statements)
3
55
3
Order By: Relevance
“…Given that sepsis is generally accompanied by acute lymphopenia (17,52,53), these findings suggested that sepsis survivors replenish the hole created in their T cell compartment. Several studies reported an association between T cell numbers and prognosis of sepsis patients beyond the acute disease phase (17,54,55), leading to the proposal that persistent lymphopenia could serve as a biomarker for late mortality in sepsis (17,55). In principle, the absence of lymphopenia in the present patient cohort is in agreement with that notion, given that all 12 patients were alive at the 28-d follow-up upon discharge from the postacute care hospital (Table II).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Given that sepsis is generally accompanied by acute lymphopenia (17,52,53), these findings suggested that sepsis survivors replenish the hole created in their T cell compartment. Several studies reported an association between T cell numbers and prognosis of sepsis patients beyond the acute disease phase (17,54,55), leading to the proposal that persistent lymphopenia could serve as a biomarker for late mortality in sepsis (17,55). In principle, the absence of lymphopenia in the present patient cohort is in agreement with that notion, given that all 12 patients were alive at the 28-d follow-up upon discharge from the postacute care hospital (Table II).…”
Section: Discussionsupporting
confidence: 80%
“…Another factor that is likely to persistently affect the adaptive immune system of the sepsis patient is the contraction of the T cell clonal repertoire as a consequence of early apoptotic T cell loss. As argued previously (17,22,55), the irreversible loss of T cell clones during early sepsis causes a contraction of the T cell repertoire that can compromise the ability of the host to react to ensuing infections. According to that scenario, "prosurvival" cytokines, such as IL-7 or IL-15, which prevent early T cell apoptosis and show high efficacy in rodent models of sepsis (13,56,73), are promising therapeutics that are already being tested in the clinic.…”
Section: Discussionmentioning
confidence: 84%
“…In sepsis, IL-15 blocked the apoptosis of CD8 + T cells and increased the abundance of Bcl-2 while decreasing Bim and Puma (343). However, patients with sepsis with severe lymphopenia had downregulated Bcl-2 mRNA expression in peripheral blood mononuclear cells, despite increased plasma IL-15 concentrations (344). Thus, further studies are needed to understand the potential role of IL-15 in sepsis.…”
Section: Maintaining T Cell Survival For Therapeutic Purposementioning
confidence: 99%
“…Every lymphocyte subpopulation was affected (except regulatory T cells, see below). Most importantly, the extent of this lymphopenia has been shown to correlate with the development of HAI and/or death at 28 days . Importantly, this lymphopenia may last for several weeks after the onset of sepsis and this lack of recovery was associated with delayed infectious complications .…”
Section: Lymphocytesmentioning
confidence: 99%